Social judgments at the intersection of class and gender across cultures - Marie Isabelle Weißflog; Lusine Grigoryan; Wilhelm Hofmann (PLoS ONE, 2026)
To address social injustice, it is crucial to understand the intersecting social dimensions that contribute to it, such as gender, race, and class. While intersections of race and gender are well-studied, class remains underexplored in social psychology. This research investigates how class (measured by education, income, and occupational status) and gender influence interpersonal attitudes regarding likability, respect, and social distance across different cultures. We present results from factorial survey experiments in eight countries (Armenia, Australia, Brazil, Germany, India, Russia, UK, US) with different gender norms and inequality levels. High education and income influenced attitudes towards women (vs. men) more positively, and low income and occupational status influenced attitudes towards men (vs. women) more negatively. In countries with more conservative gender norms, these differences were stronger. General inequality also impacted status- and gender-based attitudes. Our findings demonstrate that gender and class interact differently across cultures, contributing to discourses on intersectionality and informing social equality and policy interventions.